Influence of sudden salinity variation on the physiology and domoic acid production by two strains of Pseudo‐nitzschia australis. Issue 1 (19th November 2018) - Ayache, Nour; Hervé, Fabienne; Martin‐Jézéquel, Véronique; Amzil, Zouher; Caruana, Amandine M. N.
Abstract : Several coastal countries including France have experienced serious and increasing problems related to Pseudo‐nitzschia toxic blooms. These toxic blooms occur in estuarine and coastal waters potentially subject to fluctuations in salinity. In this study, we document for the first time the viability, growth, photosynthetic efficiency, and toxin production of two strains of Pseudo‐nitzschia australis grown under conditions with sudden salinity changes. Following salinity variation, the two strains survived over a restricted salinity range of 30–35, with favorable physiological responses, as the growth, effective quantum yield and toxin content were high compared to the other conditions. In addition, high cellular quotas of domoic acid (DA) were observed at a salinity of 40 for the strain IFR‐PAU‐16.1 in comparison with the other strain IFR‐PAU‐16.2 where the cell DA content was directly released into the medium. On the other hand, the osmotic stress imposed at lower salinities, 20 and 10, resulted in cell lysis and a sudden DA leakage in the medium. Intra‐specific variability was observed in growth and toxin production, with the strain IFR‐PAU‐16.1 apparently able to withstand higher salinities than the strain IFR‐PAU‐16.2. On the whole, DA does not appear to act as an osmolyte in response to sudden salinity changes. Since most of the shellfish harvesting areas of bivalve molluscs in France are located in areas where the salinity generally varies between 30 and 35, Pseudo‐nitzschia australis blooms might potentially impact public health and commercial shellfish resources in these places.